2008
DOI: 10.1017/s0025315408001306
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of phytoplankton assemblages, size spectra and diversity during the wane of aPhaeocystis globosaspring bloom in hydrologically contrasted coastal waters

Abstract: The space-time dynamic of phytoplankton diversity and succession was investigated during the wane of a Phaeocystis globosa spring bloom in four distinct hydrological sub-systems of the eastern English Channel. Nutrients, chlorophyll-a concentrations, and phytoplankton composition, standing stocks, size spectra and diversity were monitored during three key periods in 2003: late spring, early summer and summer. Two consecutive diatom assemblages were observed, respectively dominated by: (i) small colonial specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 68 publications
1
18
0
1
Order By: Relevance
“…por sobre las otras especies debido a que de las mencionadas anteriormente, es aquella con menor razón S/V. Por lo tanto, posee una constante de saturación media (Ks) para el Si(OH)4 más baja y necesita menores concentraciones de ácido silícico para desarrollarse de manera óptima (Reynolds, 2006;Alves-de-Souza et al, 2008;Schapira et al, 2008).…”
Section: Discussionunclassified
“…por sobre las otras especies debido a que de las mencionadas anteriormente, es aquella con menor razón S/V. Por lo tanto, posee una constante de saturación media (Ks) para el Si(OH)4 más baja y necesita menores concentraciones de ácido silícico para desarrollarse de manera óptima (Reynolds, 2006;Alves-de-Souza et al, 2008;Schapira et al, 2008).…”
Section: Discussionunclassified
“…As the domoic acid producing Pseudo-nitzschia genus has been previously observed in the study area (Antajan et al, 2013;Schapira et al, 2008), total domoic acid (i.e. dissolved and particulate) in seawater was quantified in both tanks using ASP ELISA kits (Biosense Laboratories, Bergen, Norway).…”
Section: Hydrobiological Parametersmentioning
confidence: 99%
“…P. globosa degradation in favour of spring to summer diatom assemblages (Pseudo-nitzschia sp., Guinardia sp. ; Rousseau et al, 2002;Schapira et al, 2008;Seuront et al, 2006) is highlighted by high pheopigment contribution to total pigments (i.e. 78-93% of chlorophyll a + pheopigments).…”
Section: Environmental Contextmentioning
confidence: 99%
“…The recurrent massive proliferation of the Haptophyte Phaeocystis globosa is associated to the surplus of nitrogen and silicate limitation atlate winter (Peperzak et al, 1998). Abundant populations of colonial diatoms and dinoflagellate grazers are observed before and after the P. globosa bloom (e.g., Schapira et al, 2008;Grattepanche et al, 2011a,b and references therein). A winter-summer succession study of planktonic protists, by means of 18S rRNA gene high-throughput sequencing approach, suggested that the previously well-established food web concept in the EEC based on predator-prey (e.g., grazer-phytoplankton) interactions is "just a part of the ecological picture" and in fact several organisms using a variety of previously "overlooked" strategies, such as parasitism and saprotrophy, were abundant members of the planktonic community .…”
Section: Introductionmentioning
confidence: 99%